Desarrollo de un contornímetro - Andrada Contardi, Flavio (Comisión Nacional de Energía Atómica. Instituto Balseiro, 2004)
Fil. Andrada Contardi, Flavio. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina